Motion retiming by using bilateral time control surfaces. (April 2015) - Yoo, Innfarn; Abdul Massih, Michel; Ziamtsov, Illia; Hassan, Raymond; Benes, Bedrich
Abstract: Motion retiming is an important tool used to edit character animations. It consists of changing the time at which an action occurs during an animation. One example might be editing an animation of a person playing football to change the precise time at which the ball is kicked. It is, nevertheless, a non-trivial task to retime the motion of a set of joints, since spatio-temporal correlation exists among them. It is especially difficult in the case of motion capture, when there are forward kinematic keys on every frame, to define the motion. In this paper, we present a novel approach to motion retiming that exploits the proximity of joints to preserve the motion coherence when a retiming operation is performed. We introduce the bilateral time control surface (BTCS), a framework that allows users to intuitively and interactively retime motion. The BTCS is a free-form surface, located on the timeline, that can be interactively deformed to move the action of a particular joint to a certain time, while preserving the coherency and smoothness of surrounding joints. The animation is retimed by manipulating successive BTCSs, and the final animation is generated by resampling the original motion by time spans defined by the BTCSs. Abstract : Graphical abstract: Abstract : Highlights: Introducing a new retiming formulation that can easily control motion curves and keyframes. An interactive and intuitive retiming interface without the need for modifying motion curves independently. Bilateral filtering for ensuring that edits are applied within a character's topological distance on a time surface. A new visualization technique of spatio-temporal motion data in 3D space.